Carbon Aerogels From Softwood Kraft Lignin for High Performance Supercapacitor Electrodes - Karaaslan, Muzaffer A.; Lin, Li-Ting; Ko, Frank; Renneckar, Scott (Frontiers in Materials, 2022)
Porous carbon materials derived from plant biomass offer great promise towards developing sustainable and advanced renewable materials for energy applications. Lignin is as an abundant and renewable aromatic biopolymer with high carbon content and chemical functionality for crosslinking, which make lignin a promising alternative for environmentally-friendly carbon aerogel production. In this study, carbon aerogels were produced using an industrial softwood kraft lignin isolated from renewable forest resources. Crosslinked lignin gels were synthesized using an epoxy compound and converted into carbon aerogels with subsequent sol-gel processing, supercritical drying and pyrolysis steps. The effect of lignin-to-crosslinker ratio on the chemical, physical and structural properties of resulting carbon aerogels were investigated. The bulk density of carbon aerogels increased as the lignin content increased from 56 wt.% to 87 wt. % and ranged from 0.45 to 0.83 g/cm3, respectively. FTIR results showed that crosslinked network structure was promoted when the lignin-to-crosslinker ratio was higher, which impacted the porous texture of resulting carbon aerogels as evidenced by SEM analysis. XRD analysis was used to correlate degree of graphitization and lignin content, which impacted the electrical conductivity and ion-charge transfer in carbon electrodes. To evaluate the hierarchical porous structure and determine the BET surface area and pore volume, N2 and CO2 gas adsorption experiments were conducted. Carbon aerogels with 81 wt.% and 87 wt.% lignin had superior structural characteristics, which further improved with surface activation with KOH resulting in 1609 m2/g for BET surface area, 0.98 cm3/g for total pore volume and 0.68 cm3/g for micropore volume. The electrochemical tests of electrodes assembled from 87 wt% lignin carbonized sample with a specific capacitance of 122 F/g at 1A/g had better performance compared to a commercial activated carbon (74 F/g with 845 m2/g BET) and resorcinol-formaldehyde based carbon aerogel (61 F/g with 1071 m2/g BET area), while maintaining ~90% of its capacitance after 5000 charge-discharge cycles. Surface activation of lignin carbon aerogels further boosted the capacitance properties, an outstanding energy density of 3.2 Wh/kg at 209.1 W/kg power density were obtained for the supercapacitor electrodes built from the A-CA-L87 activated carbon aerogel.